THE EFFICIENCY OF PUBLIC RELATIONS ADMINISTRATION AND PUBLICATION IN THE IRAQI NATIONAL OLYMPIC COMMITTEE FROM THE VIEWPOINT OF CENTRAL ASSOCIATIONS - Shakir, Salah Wahab (International Journal of Psychosocial Rehabilitation, 2020)
The existence of the public relations and publication team that is considered the active administrative ring in the process of assuring the communication between a given agency and its audience and creating the shared understanding between them. This study aims to (1) construct a questionnaire thatmeasures the efficiency of the public relations administration and publication in the Iraqi National Olympic committee, and (2) assess the level of the efficiency of public relations administration and publication in Iraqi National Olympic Committee. A descriptive design was used to guide this study. The study included a purposive sample of (120) members of the central associations in addition to the members of the associations. Data were analyzed using the statistical package for social sciences (SPSS) for windows, version 24, the researcher found that the questionnaire of efficiency of management of public relations and publication in the Iraqi National Olympic Committee was reliable. The study results revealed that participants expressed highest scores for the item (Is there a special body or department for public relations and publication in the Olympic Committee) versus the item (Is the public relations and publication in the Olympic Committee considered as an active swivel between you) which scored lowest. There is a lack of awareness of the importance of the tasks and responsibilities assumed upon the Department of Public Relations and Information. Moreover, the organizational relations between the Olympic Committee and its audience are almost weak and ineffective.